Comparison Between Efficacy Outcomes Of Covalent Versus Non Covalent Bruton Tyrosine Kinase (Btk) Inhibitor Treatments For Double-Exposed Chronic Lyhmpocitic Leukemia And Small Lymphocitic Lymphoma Patients: A Systematic Review - Ogek Dwi Shavitri; Bgs Gde Ariesta Darmahendra; I Gusti Sri Agung Jaya Kusumadewi (Eduvest - Journal of Universal Studies, 2026)
Background: Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is a mature B-cell malignancy. Covalent Bruton tyrosine kinase inhibitors (cBTKis) such as ibrutinib, acalabrutinib, and zanubrutinib have improved outcomes but are limited by resistance mutations at the BTK C481 site. Non-covalent BTK inhibitors (ncBTKis) like pirtobrutinib were developed to overcome this resistance. This review compares clinical outcomes between covalent and non-covalent BTK inhibitors in CLL/SLL. Methods: A systematic search of MEDLINE, CENTRAL, and EMBASE identified studies within the last 10 years evaluating cBTKis and ncBTKis in CLL/SLL. Eligible studies reported efficacy outcomes, including complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD). Quality was assessed using the Newcastle–Ottawa Scale.Results: Four studies involving 137 patients met inclusion criteria. Among ncBTKis, pirtobrutinib showed 70% PR and 11% SD, while nemtabrutinib showed 25% PR without CR. Covalent BTKi combinations achieved higher CR rates: ibrutinib + venetoclax (CR 55%, PR 45%) and acalabrutinib + obinutuzumab (CR 50%). PD rates were inconsistently reported.Conclusion: Covalent BTKi-based combinations produced deeper responses than ncBTKi monotherapy, likely due to synergistic mechanisms and earlier treatment lines. Non-covalent BTKis remain valuable for patients with cBTKi resistance but achieve limited CRs when used alone. Future trials combining ncBTKis with BCL-2 inhibitors or anti-CD20 antibodies may enhance remission depth and durability in refractory CLL/SLL.